Pathologies of the skin and its appendages in endocrine diseases - Hubert Arasiewicz; Martyna Zbiciak-Nylec; Ligia Brzezińska-Wcisło (Termedia Publishing House, 2016)
Patients suffering from endocrine disorders often present a wide profile of skin lesions. In hyperthyroidism we observe hair loss, lower leg myxedema and onycholysis or, in the case of hormone deficiency, generalized swelling of the skin, which becomes cold and pale. Primary hyperparathyroidism is revealed by pruritus, presence of chronic urticaria or deposition of amorphous calcium salts. In hypoparathyroidism, the skin is dry while the nails become very brittle. Skin lesions in diabetes include necrobiosis lipoidica, granuloma annulare, scleroderma-like diabetic edema and acanthosis nigricans. Overactive pituitary gland is often manifested as acromegaly with hypertrophy of soft tissue thickening and hypertrichosis. The skin in the early stages of hypopituitarism feels swollen, is pale yellow and oily, and finally becomes alabaster and dry. The characteristic features of Cushing syndrome are central obesity, lunar face, buffalo hump, and striae. In Addison's disease we observe hyperpigmentation. Hyperandrogenism in women leads to acne, hirsutism and virilization.